2016
DOI: 10.1002/ardp.201600038
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Antiviral Activity of Novel Phosphorylated Derivatives of Didanosine Against Newcastle Disease Virus in Chicken

Abstract: A series of novel phosphorylated derivatives of didanosine were designed and docking studies were performed with a fusion protein of the Newcastle disease virus (NDV), to develop antiviral compounds against NDV. Based on the docking scores and binding affinities, three derivatives were selected. These compounds were synthesized and characterized by IR, (1) H, (13) C, (31) P, and CHN analysis and mass spectra. They were assessed for their in vitro antiviral activity in DF-1 cells; DDI-10 showed better antiviral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Phosphorylated didanosine derivates are designed [ 29 , 31 , 83 ] to overcome the disadvantages of didanosine, such as a short plasma half-life, low bioavailability, and dose-dependent cellular toxicities; it is unstable in its acidic conditions [ 84 ] and has poor permeability through intestinal epithelium and low oral bioavailability [ 85 ]. In one study, phosphorylated didanosine derivate DDI-10 was chosen from a series of designed derivates and showed antiviral activity against NDV in vitro, as evidenced by a significant reduction in plaque formation and cytopathic effects [ 86 ].…”
Section: Didanosinementioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylated didanosine derivates are designed [ 29 , 31 , 83 ] to overcome the disadvantages of didanosine, such as a short plasma half-life, low bioavailability, and dose-dependent cellular toxicities; it is unstable in its acidic conditions [ 84 ] and has poor permeability through intestinal epithelium and low oral bioavailability [ 85 ]. In one study, phosphorylated didanosine derivate DDI-10 was chosen from a series of designed derivates and showed antiviral activity against NDV in vitro, as evidenced by a significant reduction in plaque formation and cytopathic effects [ 86 ].…”
Section: Didanosinementioning
confidence: 99%
“…In vivo, in NDV-infected chicken, it was shown that superoxide dismutase and catalase were significantly raised, and lipid peroxidation and HA titer levels were decreased upon treatment with 1.5 mg/kg BW of DDI-10 compared to 3 mg/kg BW of DDI [ 86 ]. Histopathological alterations in NDV-infected tissues were restored in chickens treated with DDI-10.…”
Section: Didanosinementioning
confidence: 99%
“…Previously several researchers proved the NDV inhibitory activity of aminated nucleosides . It was found that amino acid esters are used as pro‐drugs of nucleoside namely Valacyclovir, L ‐valine can easily diffuse across the intestine mediated by the intestinal proton‐coupled peptide transporter which resulted in increase of oral absorption, such as Acyclovir and Ganciclovir …”
Section: Introductionmentioning
confidence: 99%